New Eurycorypha species (Orthoptera: Tettigonoidea: Phaneropteridae; Phaneropterinae from East Africa - Hemp, Claudia (Zootaxa, 2017)
Eight Eurycorypha species are newly described for Tanzania. These are E. binasuta n. sp. from the Nguru and Udzungwa Mountains, E. curviflava n. sp. from the eastern slopes of Mt Kilimanjaro, E. divertata n. sp., E. elongata n. sp. and E. flexata n. sp. from the East Usambara Mountains, E. pseudomeruensis n. sp. from Central-west Tanzania and western Kenya, E. pseudovaria n. sp. from the West and East Usambara Mountains and E. victoriae n. sp. from the shores of Lake Victoria. Further the hitherto unknown females of two Eurycorypha, E. combretoides Hemp and E. ligata Hemp are described. A key to the males of Tanzania and Kenya is provided.